REPRESENTASI KARAKTER BELA NEGARA DALAM SERAT TRIPAMA SEBAGAI SARANA PENDIDIKAN KARAKTER KEPADA SISWA - Bagus Wahyu Setyawan; Rahmawati Mulyaningtyas; Muhammad Rohmadi (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2021)
Javanese literature is a product from ideas of author and Javanese poet which contain a great value. Many kind of Javanese literature has created from author and being a phenomenal works because contain morality values. One of phenomenal Javanese literature is Serat Tripama from KGPAA Mangkunegara IV. Serat Tripama tell us about three characters of wayang, that are Suwanda, Kumbakarna, and Karna. When we look moredeeper into Serat Tripama, there are contain good messages about nationalism values, it can look in depiction of three characters who was talking about. Serat Tripama can use to be a means to introducting national spirit characters for young generation. That way is related with the last condition, when many young generation having less of sense of belonging with their nation. Therefore, this way can use to introduction the Javanese literature works to the young generations, because in this globalization era most of our young generation preference like to learn the other works from the other culture than knowing and learning about their own culture, in this context is Javanese literature